2019
DOI: 10.1111/anzs.12270
|View full text |Cite
|
Sign up to set email alerts
|

Using hidden Markov models with raw, triaxial wrist accelerometry data to determine sleep stages

Abstract: Accelerometry is a low-cost and noninvasive method that has been used to discriminate sleep from wake, however, its utility to detect sleep stages is unclear. We detail the development and comparison of methods which utilise raw, triaxial accelerometry data to classify varying stages of sleep, ranging from sleep/wake detection to discriminating rapid eye movement sleep, stage one sleep, stage two sleep, deep sleep and wake. First-and second-order hidden Markov models (HMMs) with time-homogeneous and time-varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Based on an exploratory analysis of our data, we observed that transition between sleep states is rare compared to remaining in the same state for prolonged periods of time. Hence, when using approaches like Hidden Markov Models (HMM) as in Trevenen et al 13 , the transition probability matrix is heavily diagonal and HMMs do not provide any advantage under such scenarios. Therefore, we trained discriminative models for every time interval based on engineered features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on an exploratory analysis of our data, we observed that transition between sleep states is rare compared to remaining in the same state for prolonged periods of time. Hence, when using approaches like Hidden Markov Models (HMM) as in Trevenen et al 13 , the transition probability matrix is heavily diagonal and HMMs do not provide any advantage under such scenarios. Therefore, we trained discriminative models for every time interval based on engineered features.…”
Section: Discussionmentioning
confidence: 99%
“…Level Our sleep classification approach is most similar to that of Trevenen et al 13 . Based on an exploratory analysis of our data, we observed that transition between sleep states is rare compared to remaining in the same state for prolonged periods of time.…”
Section: F1 (%) Ap (%) F1 (%) Ap (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are multiple joints between the wrist and torso in sleep staging and the human body, restoring the overall body posture with the wrist is difficult. In 2019, Trevenen et al attempted to improve the accuracy of recognition with machine-learning algorithms [ 135 ]. In the same year, Walch et al also attempted to analyze raw acceleration data from Apple Watch to analyze sleep, but the specificity was not satisfactory [ 136 ].…”
Section: Biomechanical Signal Monitoringmentioning
confidence: 99%
“…Computational methods used to extract valuable information for screening purposes are mainly based on signal processing and Artificial Intelligence (AI). Common features extracted are averages, ranges, angles, skewness, kurtosis and Wavelet coefficients [ 32 , 33 ], whereas classifiers used are K-Nearest Neighbor (KNN) [ 34 ], Decision Tree, Random Forest, Support Vector Machine [ 10 , 24 , 34 , 35 , 36 ] and Hidden Markov Models (HMMs) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%